Antibodies to the human 60 kDa heat-shock protein in patients with schizophrenia - Kilidireas, K.; Sadiq, S.A.; Gorig, A.D.; Latov, N.; Strauss, D.H.; Hashim, G.A.; Gorman, J.M. (The Lancet (British edition), 1992)
Immune mechanisms are thought to be important in a subpopulation of patients with schizophrenia. We examined the specificity of neural antibodies in patients with schizophrenia to identify a possible antigen. Serum antibodies from patients with schizophrenia and control subjects were tested for binding to protein extracts of human neuroblastoma cells by western blot. Protein antigens were characterised by aminoterminal and internal aminoacid sequence analysis. 14 of 32 (44%) otherwise healthy patients with schizophrenia had antibodies to a neuroblastoma protein of molecular weight 60 kDa. By partial sequence analysis, this protein was identified as the 60 kDa human heat-shock protein (hsp) that is the P1 mitochondrial protein, and which is 50% homologous to the mycobacterial 65 kDa hsp. Antigens that crossreact with hsp65 have been implicated in the pathogenesis of adjuvant-induced arthritis in rats and autoimmune diabetes in mice. Of 100 normal subjects or disease controls, antibodies to hsp60 were found in only 8 patients, all of whom had active infectious or inflammatory disease. Our results support the presence of abnormal immune reactivity involving hsp60 in a subset of patients with schizophrenia. The immune response may be related to the pathogenesis of the disease.